Anestesia total intravenosa en un sistema de lazo cerrado: Reporte del primer caso en Colombia (2013)
ABSTRACT: Total intravenous anesthesia is a widely used technique that relies on the use of intravenous anesthetics, propofol being the most frequently used and studied. At present, there are pharmaceutical and pharmacokinetic tools that are used to generate mathematical models to ensure the safe and moderately effective use of this technique. However, the depth of anesthesia is determined purely on the clinical findings and this requires neurological monitoring such as the bi-spectral index (BIS) in order to correlate the data derived from the pharmacokinetic models used for the administration of the anesthetic with the determination of its desired clinical effect. We designed an operating system for automated control of the propofol infusion that provides feedback on the basis of the data generated by the BIS monitor. The system is programmed to increase or decrease the propofol infusion within a specific BIS range and, consequently, in accordance with the needs of the individual patient. We describe anesthetic management using this technique in a female patient taken to surgery for prosthetic mammary implantation under general anesthesia at the University Hospital. An intraoperative record was generated including the depth of anesthesia and its action on propofol concentration at the effective site using the automated administration and control system. We concluded that the use of closed-loop total intravenous anesthesia under neurologic monitoring is the next step in the evolution of this technique. It is less reliant on the phar-macokinetic models available at present, and is better suited to adapt to the specific needs of individual patients and to the type of surgical intervention.